Method for constructing mixed matrix membrane with continuous channels by regulating and controlling microphase separation structure
Regulating microphase separation structures in block copolymers with imidazolyl ionic liquids enhances CO2 transmission and solubility, addressing the permeability-selectivity trade-off in CO2 separation membranes, resulting in improved carbon capture materials.
Patent Information
- Application Number
- CN202411551372.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-11-01
AI Technical Summary
Current membrane materials for CO2 separation exhibit a 'trade-off' between permeability and selectivity, limiting their effectiveness in carbon capture and storage (CCUS) technologies, and there is a need for improved materials with high permeability and selectivity.
A method involving tunable block copolymers with regulated microphase separation structures and imidazolyl ionic liquids to form continuous channels, enhancing CO2 transmission and solubility through controlled hydrogen bonding and CO2-philic functionalization.
The method results in membranes with improved CO2 adsorption and separation performance, thermal stability, and selective CO2 transmission by forming continuous nanoscale channels and CO2-philic networks.
Smart Images

Figure CN119215681A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of gas separation, and relates to a method for constructing a mixed matrix membrane with continuous channels by regulating a microphase separation structure. Background Art
[0002] In order to cope with the harm caused by the greenhouse effect, carbon capture, utilization and storage (CCUS) technology is an important path to achieve carbon neutrality, and CO2 separation is the first step in carbon capture, utilization and storage (CCUS) technology. Effective CO2 capture technologies include low-temperature separation, chemical absorption, physical adsorption and membrane separation. Among them, membrane separation is widely used due to its advantages such as no pollution, low energy consumption and good effect. Its main challenge lies in the preparation of membrane materials with high separation efficiency. At present, due to the low separation performance of membrane materials, its further development is limited. The development and preparation of membrane materials with high permeability and high selectivity is a hot topic in current research. Traditional polymer materials have good film-forming properties and low cost, and are the main body of membrane materials. However, the "trade-off" effect of permeability and selectivity limits the application of membrane materials. Research based on polymers is to continuously improve the permeability and selectivity of membranes.
[0003] The ether-containing block copolymer membrane has the unique properties of both plastic and rubber. The presence of its microphase separation structure provides additional free volume and a more precise separation process, which is conducive to gas permeation. The soft segment contains ether bonds, which can increase the solubility of CO2 and ensure mechanical strength. The degree of microphase separation of polyether polyurethane block copolymers can be regulated by adjusting the different volume fractions of monomers. Therefore, the microphase separation structure can be used to form a channel for enhanced CO2 transmission. Researchers have proposed that the two PIs in the polymer blend membrane are separated by different compatibilities to form their own polymer phases, while MOFs particles, due to the induction of the PI attached to the surface, will preferentially choose to enter the same PI matrix phase, thereby providing a fast channel for them. Some researchers have also proposed an ion conduction membrane with a microphase separation structure, which uses one or more hydrophobic and hydrophilic polymer resins as raw materials, induces the aggregation of hydrophobic phases and hydrophilic phases during the solvent evaporation process, and forms an ion conduction membrane with a microphase separation structure of hydrophobic and hydrophilic regions (CN107546398A). Some researchers have also proposed grafting non-polar SBS onto amorphous POEM, which can increase the CO2-philic area and improve the carbon dioxide separation performance without affecting the mechanical properties of the membrane.
[0004] Ionic liquids, especially ionic liquids at room temperature, are ideal materials for carbon capture due to their low volatility and are often used in the absorption field. In particular, imidazole-based ionic liquids can promote the transfer effect of imidazole groups after blending with polymers, thereby improving the separation performance of the membrane. Mixing ionic liquids with polymers and utilizing the strong and weak interactions between polymer fragments and ionic liquids to produce membrane materials is an effective method. At present, some ionic liquid and polymer blend membranes have been used in the field of gas separation.
[0005] Therefore, we propose to use tunable block copolymers as templates. Due to the different hydrogen bonding interactions between the soft and hard segments of the block copolymers, the microphase separation structure of the block copolymers can be regulated by adjusting the polarity strength of the soft segment, the molecular weight of the soft segment and the mass fraction of the hard segment, thereby forming a continuous morphology and constructing a continuous nanoscale transmission channel to enhance the gas diffusion selectivity; the introduction of ionic liquids with CO2-philic functional groups can realize the CO2-philic functionalization of the channel and improve the solubility selectivity of CO2. At the same time, due to the different polarity strengths of ionic liquids, they interact strongly with the polymer chains, and the microphase separation structure can be further regulated to form a CO2-philic network channel. In addition, the presence of polar urethane and electron-donating -NH2 groups in the polyurethane membrane structure can enhance the solubility of CO2 through strong dipole-quadrupole interactions with CO2 molecules, thereby enhancing the gas separation performance. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a method for constructing a mixed matrix membrane with continuous channels by regulating the microphase separation structure.
[0007] The technical solution of the present invention:
[0008] A method for constructing a mixed matrix membrane with continuous channels by regulating a microphase separation structure, comprising the following steps:
[0009] (1) Preparation of polyurethane block copolymer membrane microphase separation structure
[0010] H1: Place the polyether polyol in a vacuum oven for dehydration, and maintain vacuum pressure at 80-90℃ for 3-6 hours;
[0011] H2: 5-30 parts of polyether polyol, 2.5-15.01 parts of isocyanate, 0.8-5 parts of isocyanate ethyl acrylate are used, and after heating under a nitrogen atmosphere, 0.02-0.06 parts of catalyst dibutyltin dilaurate (DBTDL) are added to obtain propylene diisocyanate prepolymer after reaction;
[0012] H3: Continue to add 0.02-0.3 parts of 2-amino-5-fluorophenylboric acid / terbium complex, 0.872-5.229 parts of 1,6-hexanediamine, and 0.04-0.7 parts of 2,5-bis(4-aminophenoxy)biphenyl CAS No. 94148-67-1, and react with stirring under nitrogen atmosphere to obtain a polyurethane block copolymer;
[0013] H4: The polyurethane block copolymer is washed with 50 wt.% methanol and 50 wt.% aqueous solution, precipitated to remove unreacted monomers or low molecular weight polymers, and vacuum dried at 60-70°C to obtain the polyurethane block copolymer.
[0014] The polyether polyol is one of PEG, PPG, PTMG and PTMEG, and the molecular weight is one of 1000, 2000, 4000 and 6000, preferably PEG (2000).
[0015] The isocyanate is selected from one of IPDI, HDI, MDI and TDI, with a mass fraction of 20-60wt.%, preferably MDI (45wt.%).
[0016] The reaction temperature in H2 is 70-90°C, and the reaction time is 180-240min.
[0017] The reaction temperature in H3 is 60-80°C and the reaction time is 100-150 minutes.
[0018] The preparation method of the 2-amino-5-fluorophenylboric acid / terbium complex is as follows:
[0019] According to weight, 10-30 parts of 2-amino-5-fluorophenylboric acid, 2-6 parts of terbium nitrate pentahydrate and 160-300 parts of ethanol are mixed, and the temperature is increased for reaction. After the reaction is completed, the ethanol is distilled off, and then vacuum drying is performed to obtain a 2-amino-5-fluorophenylboric acid / terbium complex.
[0020] The reaction temperature is 40-50°C and the reaction time is 80-160 minutes.
[0021] (2) Preparation of polyurethane block copolymer membranes with imidazolyl ionic liquids
[0022] S1: adding 0.3-3 parts of polyether polyurethane block copolymer to 10-100 parts of N,N-dimethylformamide solution to completely dissolve the block copolymer to obtain a block copolymer solution;
[0023] S2: slowly drop 0.0529-0.75 parts of ionic liquid into the block copolymer solution, and stir magnetically to completely dissolve the ionic liquid therein to obtain a casting solution;
[0024] S3: Add the casting solution into a polytetrafluoroethylene culture dish, place it in a vacuum condition at 40-50°C to remove the residual solvent, and obtain a mixed matrix membrane with continuous channels.
[0025] The ionic liquid is selected from one of [EMIM][PF6], [BMIM][PF6], [HMIM][PF6], [EMIM][TF2N], [BMIM][TF2N], [HMIM][TF2N], [EMIM][DCA], [BMIM][DCA], and [HMIM][DCA], preferably [HMIM][PF6].
[0026] Reaction mechanism
[0027] 1. Reaction of propylene diisocyanate prepolymer and 2-amino-5-fluorophenylboric acid / terbium complex:
[0028] The isocyanate group (-NCO) in the propylene diisocyanate (ADI) prepolymer undergoes an addition reaction with the amino group (-NH2) in the 2-amino-5-fluorophenylboric acid / terbium complex; the reaction generates a urea bond (-NH-CO-NH-), and the 2-amino-5-fluorophenylboric acid / terbium complex is grafted onto the prepolymer.
[0029] 2. Reaction of propylene diisocyanate prepolymer and 2,5-bis(4-aminophenoxy)biphenyl:
[0030] The isocyanate groups in the ADI prepolymer undergo an addition reaction with the amino groups in 2,5-bis(4-aminophenoxy)biphenyl; urea bonds are also generated, and the biphenyl groups are introduced into the prepolymer.
[0031] 3. Formation of block copolymers:
[0032] The products of the above two reactions are further polymerized to form block copolymers; the soft segments are composed of polyether segments, and the hard segments are composed of rigid structures (such as biphenyl groups) connected by urea bonds.
[0033] 4. Introduction of imidazolyl ionic liquids (ILs):
[0034] ILs are introduced into block copolymers by physical mixing or chemical bonding; ILs have high affinity and solubility for CO2 and can enhance the material's adsorption capacity for CO2.
[0035] Compared with the prior art, the present invention has the following significant effects:
[0036] 1. Regulate the degree of microphase separation:
[0037] By adjusting the ratio of soft segment to hard segment, the strength of hydrogen bonding between -NH group in hard segment and -C=O group and ester group in soft segment controls the degree of microphase separation. Soft segment is usually composed of flexible segments such as polyether or polyester, while hard segment is composed of urea bond generated by reaction of diisocyanate and small molecule chain extender. The introduction of fluorophenylboric acid / terbium complex and rigid biphenyl group can affect the ratio and distribution of soft and hard segments, thereby adjusting the degree of microphase separation and forming continuous channels.
[0038] 2. The introduction of imidazole-based ionic liquids further regulates the microphase separation structure. Due to the different polarities of ionic liquids, they interact strongly and weakly with polymer chains. At the same time, the microphase separation structure of the polyurethane block copolymer membrane forms a continuous structure, and the introduction of ionic liquids with CO2-philic functional groups can realize the CO2-philic functionalization of the channel to form a CO2-philic network channel, further improving the material's CO2 adsorption and separation performance.
[0039] 3. Enhance the thermal stability of materials:
[0040] The fluorine atoms in the fluorophenylboric acid / terbium complex can form a stable coordination bond with terbium. This structure has high thermal stability and can maintain the structure and performance of the material stable at high temperatures. The introduction of the biphenyl group increases the rigidity of the molecular chain, increases the glass transition temperature (Tg) of the material, and further enhances the thermal stability of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is the AFM image of the ILs / PU film in the example.
[0042] Figure 2 These are AFM images of pure PU film and ILs / PU film in the examples, where (a) is PU-1 film, (b) is PU-2 film, (c) is 10wt.% ILs / PU-2 film, (d) is 15wt.% ILs / PU-2 film, and (e) is 20wt.% ILs / PU-2 film. DETAILED DESCRIPTION
[0043] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.
[0044] Example 1
[0045] A method for constructing a mixed matrix membrane with continuous channels by regulating a microphase separation structure, wherein the operating steps are:
[0046] (1) Preparation of polyurethane block copolymer membrane microphase separation structure
[0047] H1: Dehydrate the polyether polyol in a vacuum oven and maintain vacuum at 80°C for 3 hours;
[0048] H2: 5 g of polyether polyol PEG (2000), 2.5 g of 4,4-diphenylmethane diisocyanate (MDI), and 0.8 g of ethyl isocyanate acrylate were added in a nitrogen atmosphere at 70° C. 0.02 g of catalyst dibutyltin dilaurate (DBTDL) was added, and the reaction was continued for 180 min to obtain a propenyl diisocyanate prepolymer;
[0049] H3: Continue to add 0.02 g of 2-amino-5-fluorophenylboric acid / terbium complex, 0.872 g of 1,6-hexanediamine, and 0.04 g of 2,5-bis(4-aminophenoxy)biphenyl (CAS No. 94148-67-1), and stir and react for 80 min at 60° C. in a nitrogen atmosphere to obtain a polyurethane block copolymer;
[0050] H4: The polyurethane block copolymer was washed with 50 wt.% methanol and 50 wt.% water solution, precipitated to remove unreacted monomers or low molecular weight polymers, and dried under vacuum at 60°C.
[0051] The preparation method of the 2-amino-5-fluorophenylboric acid / terbium complex is as follows:
[0052] 10 g of 2-amino-5-fluorophenylboric acid, 2 g of terbium nitrate pentahydrate and 160 g of ethanol were mixed, the reaction temperature was 40° C., and after the reaction for 80 min, the ethanol was distilled off, and then vacuum dried to obtain a 2-amino-5-fluorophenylboric acid / terbium complex.
[0053] (2) Preparation of polyurethane block copolymer membranes with imidazolyl ionic liquids
[0054] S1: Add 0.3 g of polyether polyurethane block copolymer to 10 g of N,N-dimethylformamide solution to completely dissolve the block copolymer to obtain a block copolymer solution;
[0055] S2: Slowly add 0.0529 g of [HMIM][PF6] ionic liquid to the block copolymer solution, and stir magnetically to completely dissolve the ionic liquid to obtain a casting solution;
[0056] S3: The casting solution was added to a polytetrafluoroethylene petri dish, dried at room temperature, and then placed in a 45°C vacuum oven to remove the residual solvent to obtain a membrane.
[0057] Example 2
[0058] A method for constructing a mixed matrix membrane with continuous channels by regulating a microphase separation structure, wherein the operating steps are:
[0059] (1) Preparation of polyurethane block copolymer membrane microphase separation structure
[0060] H1: Dehydrate the polyether polyol in a vacuum oven and maintain vacuum at 80°C for 3 hours;
[0061] H2: 10 g of polyether polyol PEG (2000), 3.75 g of 4,4-diphenylmethane diisocyanate (MDI), and 1 g of ethyl isocyanate acrylate were added in a nitrogen atmosphere at 70°C, and 0.03 g of catalyst dibutyltin dilaurate (DBTDL) was reacted for 200 min to obtain a propenyl diisocyanate prepolymer;
[0062] H3: Continue to add 0.03 g of 2-amino-5-fluorophenylboric acid / terbium complex, 1.162 g of 1,6-hexanediamine, and 0.1 g of 2,5-bis(4-aminophenoxy)biphenyl (CAS No. 94148-67-1), and stir and react for 100 min at 60° C. in a nitrogen atmosphere to obtain a polyurethane block copolymer;
[0063] H4: The polyurethane block copolymer was washed with 50 wt.% methanol and 50 wt.% water solution, precipitated to remove unreacted monomers or low molecular weight polymers, and dried under vacuum at 60°C.
[0064] The preparation method of the 2-amino-5-fluorophenylboric acid / terbium complex is as follows:
[0065] 15 g of 2-amino-5-fluorophenylboric acid, 3 g of terbium nitrate pentahydrate and 200 g of ethanol were mixed, the reaction temperature was 40° C., and after the reaction for 100 min, the ethanol was distilled off, and then vacuum dried to obtain a 2-amino-5-fluorophenylboric acid / terbium complex.
[0066] (2) Preparation of polyurethane block copolymer membranes with imidazolyl ionic liquids
[0067] S1: Add 0.9 g of polyether polyurethane block copolymer to 30 g of N,N-dimethylformamide solution to completely dissolve the block copolymer to obtain a block copolymer solution;
[0068] S2: Slowly add 0.122 g of [HMIM][PF6] ionic liquid to the block copolymer solution, and stir magnetically to completely dissolve the ionic liquid to obtain a casting solution;
[0069] S3: The casting solution was added to a polytetrafluoroethylene petri dish, dried at room temperature, and then placed in a 45°C vacuum oven to remove the residual solvent to obtain a membrane.
[0070] Example 3
[0071] A method for constructing a mixed matrix membrane with continuous channels by regulating a microphase separation structure, wherein the operating steps are:
[0072] (1) Preparation of polyurethane block copolymer membrane microphase separation structure
[0073] H1: Dehydrate the polyether polyol in a vacuum oven and maintain vacuum at 80°C for 4 hours;
[0074] H2: 15 g of polyether polyol PEG (2000), 7.5 g of 4,4-diphenylmethane diisocyanate (MDI), and 3 g of ethyl isocyanate acrylate were added in a nitrogen atmosphere at 75° C. 0.04 g of catalyst dibutyltin dilaurate (DBTDL) was added, and the reaction was continued for 210 min to obtain a propenyl diisocyanate prepolymer;
[0075] H3: Continue to add 0.1 g of 2-amino-5-fluorophenylboric acid / terbium complex, 2.615 g of 1,6-hexanediamine, and 0.2 g of 2,5-bis(4-aminophenoxy)biphenyl (CAS No. 94148-67-1), and stir the reaction at 65° C. in a nitrogen atmosphere for 110 min to obtain a polyurethane block copolymer;
[0076] H4: The polyurethane block copolymer was washed with 50 wt.% methanol and 50 wt.% water solution, precipitated to remove unreacted monomers or low molecular weight polymers, and dried under vacuum at 60°C.
[0077] The preparation method of the 2-amino-5-fluorophenylboric acid / terbium complex is as follows:
[0078] 20 g of 2-amino-5-fluorophenylboric acid, 4 g of terbium nitrate pentahydrate, and 240 g of ethanol were mixed, the reaction temperature was 45° C., and after the reaction for 120 min, the ethanol was distilled off, and then vacuum dried to obtain a 2-amino-5-fluorophenylboric acid / terbium complex.
[0079] (2) Preparation of polyurethane block copolymer membranes with imidazolyl ionic liquids
[0080] S1: Add 1.2 g of polyether polyurethane block copolymer to 40 g of N,N-dimethylformamide solution to completely dissolve the block copolymer to obtain a block copolymer solution;
[0081] S2: Slowly add 0.429 g of [HMIM][PF6] ionic liquid to the block copolymer solution, and stir magnetically to completely dissolve the ionic liquid to obtain a casting solution;
[0082] S3: The casting solution was added to a polytetrafluoroethylene petri dish, dried at room temperature, and then placed in a 45°C vacuum oven to remove the residual solvent to obtain a membrane.
[0083] Example 4
[0084] A method for constructing a mixed matrix membrane with continuous channels by regulating a microphase separation structure, wherein the operating steps are:
[0085] (1) Preparation of polyurethane block copolymer membrane microphase separation structure
[0086] H1: Dehydrate the polyether polyol in a vacuum oven and maintain vacuum at 85°C for 5 hours;
[0087] H2: 20 g of polyether polyol PEG (2000), 10.01 g of 4,4-diphenylmethane diisocyanate (MDI), and 4 g of ethyl isocyanate acrylate were added under nitrogen atmosphere at 85° C. 0.05 g of catalyst dibutyltin dilaurate (DBTDL) was reacted to obtain acryl diisocyanate prepolymer;
[0088] H3: Continue to add 0.2g of 2-amino-5-fluorophenylboric acid / terbium complex, 3.486g of 1,6-hexanediamine, and 0.5g of 2,5-bis(4-aminophenoxy)biphenyl (CAS No. 94148-67-1), and stir and react for 140min at 75°C in a nitrogen atmosphere to obtain a polyurethane block copolymer;
[0089] H4: The polyurethane block copolymer was washed with 50 wt.% methanol and 50 wt.% water solution, precipitated to remove unreacted monomers or low molecular weight polymers, and dried under vacuum at 60°C.
[0090] The preparation method of the 2-amino-5-fluorophenylboric acid / terbium complex is as follows:
[0091] 25 g of 2-amino-5-fluorophenylboric acid, 5 g of terbium nitrate pentahydrate, and 280 g of ethanol were mixed, and the reaction temperature was 45° C. After the reaction for 140 min, the ethanol was distilled off, and then vacuum dried to obtain a 2-amino-5-fluorophenylboric acid / terbium complex.
[0092] (2) Preparation of polyurethane block copolymer membranes with imidazolyl ionic liquids
[0093] S1: Add 1.5 g of polyether polyurethane block copolymer to 50 g of N,N-dimethylformamide solution to completely dissolve the block copolymer to obtain a block copolymer solution;
[0094] S2: slowly drop 0.591 g of [HMIM] [PF6] ionic liquid into the block copolymer solution, and stir magnetically to completely dissolve the ionic liquid therein to obtain a casting solution;
[0095] S3: The casting solution was added to a polytetrafluoroethylene petri dish, dried at room temperature, and then placed in a 45°C vacuum oven to remove the residual solvent to obtain a membrane.
[0096] Example 5
[0097] A method for constructing a mixed matrix membrane with continuous channels by regulating a microphase separation structure, wherein the operating steps are:
[0098] (1) Preparation of polyurethane block copolymer membrane microphase separation structure
[0099] H1: Dehydrate the polyether polyol in a vacuum oven and maintain vacuum at 90°C for 6 hours;
[0100] H2: 30 g of polyether polyol PEG (2000), 15.01 g of 4,4-diphenylmethane diisocyanate (MDI), and 5 g of ethyl isocyanate acrylate were added in a nitrogen atmosphere at 90° C. 0.06 g of catalyst dibutyltin dilaurate (DBTDL) was added, and the reaction was continued for 240 min to obtain a propenyl diisocyanate prepolymer;
[0101] H3: Continue to add 0.3 g of 2-amino-5-fluorophenylboric acid / terbium complex, 5.229 g of 1,6-hexanediamine, and 0.7 g of 2,5-bis(4-aminophenoxy)biphenyl (CAS No. 94148-67-1), and stir and react for 150 min at 80° C. in a nitrogen atmosphere to obtain a polyurethane block copolymer;
[0102] H4: The polyurethane block copolymer was washed with 50 wt.% methanol and 50 wt.% water solution, precipitated to remove unreacted monomers or low molecular weight polymers, and dried under vacuum at 60°C.
[0103] The preparation method of the 2-amino-5-fluorophenylboric acid / terbium complex is as follows:
[0104] 30 g of 2-amino-5-fluorophenylboric acid, 6 g of terbium nitrate pentahydrate and 300 g of ethanol were mixed, the reaction temperature was 50° C., and after the reaction for 160 min, the ethanol was distilled off, and then vacuum dried to obtain a 2-amino-5-fluorophenylboric acid / terbium complex.
[0105] (2) Preparation of polyurethane block copolymer membranes with imidazolyl ionic liquids
[0106] S1: Add 3 g of polyether polyurethane block copolymer to 100 g of N,N-dimethylformamide solution to completely dissolve the block copolymer to obtain a block copolymer solution;
[0107] S2: slowly drop 0.75 g of [HMIM][PF6] ionic liquid into the block copolymer solution, and stir magnetically to completely dissolve the ionic liquid therein to obtain a casting solution;
[0108] S3: The casting solution was added to a polytetrafluoroethylene petri dish, dried at room temperature, and then placed in a 50°C vacuum oven to remove the residual solvent to obtain a membrane.
[0109] Comparative Example 1
[0110] The other steps were the same as in Example 1 except that the 2-amino-5-fluorophenylboric acid / terbium complex and 2,5-bis(4-aminophenoxy)biphenyl were not added.
[0111] Comparative Example 2
[0112] The other steps were the same as in Example 1 except that the 2-amino-5-fluorophenylboric acid / terbium complex was not added.
[0113] Comparative Example 3
[0114] The other steps were the same as in Example 1 except that 2,5-bis(4-aminophenoxy)biphenyl was not added.
[0115] Comparative Example 4
[0116] No ionic liquid was added, and the rest was the same as in Example 1.
[0117] Gas separation performance of the obtained membrane material at an operating pressure difference of 0.3 MPa and a temperature of 298.15 K
[0118] <![CDATA[CO2 Permeability (barrer)]]> <![CDATA[CO2 / N2 selectivity]]> Example 1 409.48 81.36 Example 2 418.65 83.22 Example 3 438.00 85.65 Example 4 458.76 88.42 Example 5 489.73 92.89 Comparative Example 1 399.82 79.17 Comparative Example 2 405.76 80.52 Comparative Example 3 406.55 80.41 Comparative Example 4 359.62 47.25
[0119] Figure 1 It is shown in the figure that as the hard segment content increases, more hydrogen bonds exist between the polyurethane-C=O and polyurethane-NH groups. The hydrogen bonds between the hard segment molecular segments can promote the same orientation of the molecules to a certain extent. The molecular arrangement is directional, which is beneficial to the phase separation of the soft segment and the hard segment to form a microphase separation structure. At the same time, the introduction of fluorophenylboric acid / terbium complex and rigid biphenyl group further affects the ratio and distribution of the soft and hard segments. The gas separation performance of Example 1 is compared with that of Example 2. It is obvious that when the hard segment is 45wt.%, the CO2 / N2 separation performance of Example 2 is better. Figure 2 It is shown that the introduction of imidazolyl ionic liquid further regulates the microphase separation structure, forms a CO2-philic network channel, and further improves the material's adsorption of CO2. The gas separation performance comparison of Example 2, Example 3, Example 4 and Example 5 shows that the addition of [HMIM][PF6] ionic liquid further improves the CO2 / N2 separation performance.
[0120] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for constructing a mixed matrix membrane with continuous channels by regulating the microphase separation structure, characterized in that: Here are the steps: (1) Preparation of polyurethane block copolymer membrane microphase separation structure (1.1) Dehydrate the polyether polyol in a vacuum oven and maintain vacuum pressure at 80-90°C for 3-6 hours; (1.2) by weight, 5-30 parts of polyether polyol, 2.5-15.01 parts of isocyanate, and 0.8-5 parts of ethyl isocyanate acrylate are added under a nitrogen atmosphere after heating, and 0.02-0.06 parts of a catalyst dibutyltin dilaurate are reacted to obtain an propylene diisocyanate prepolymer; (1.3) Continue to add 0.02-0.3 parts of 2-amino-5-fluorophenylboric acid / terbium complex, 0.872-5.229 parts of 1,6-hexanediamine, and 0.04-0.7 parts of 2,5-bis(4-aminophenoxy)biphenyl CAS No. 94148-67-1, and react with stirring under nitrogen atmosphere to obtain a polyurethane block copolymer; (1.4) washing the polyurethane block copolymer with 50 wt.% methanol and 50 wt.% aqueous solution to remove unreacted monomers or low molecular weight polymers, and vacuum drying at 60-70° C. to obtain a polyether polyurethane block copolymer; (2) Preparation of polyurethane block copolymer membranes with imidazolyl ionic liquids (2.1) adding 0.3-3 parts of a polyether polyurethane block copolymer to 10-100 parts of an N,N-dimethylformamide solution to completely dissolve the polyether polyurethane block copolymer to obtain a block copolymer solution; (2.2) slowly adding 0.0529-0.75 parts of ionic liquid to the block copolymer solution, and stirring magnetically to completely dissolve the ionic liquid therein to obtain a casting solution; (2.3) The casting solution is added to a polytetrafluoroethylene culture dish and placed in a vacuum condition at 40-50° C. to remove the residual solvent, thereby obtaining a mixed matrix membrane with continuous channels.
2. The method according to claim 1, characterized in that The polyether polyol is one of PEG, PPG, PTMG and PTMEG, and the molecular weight is one of 1000, 2000, 4000 and 6000.
3. The method according to claim 1, characterized in that The isocyanate is selected from one of IPDI, HDI, MDI and TDI, with a mass fraction of 20-60wt.%.
4. The method according to claim 1, characterized in that: The reaction temperature in step (1.2) is 70-90°C, and the reaction time is 180-240 min.
5. The method according to claim 1, characterized in that The reaction temperature in step (1.3) is 60-80°C and the reaction time is 100-150 min.
6. The method according to claim 1, characterized in that The preparation method of the 2-amino-5-fluorophenylboric acid / terbium complex is as follows: According to weight, 10-30 parts of 2-amino-5-fluorophenylboric acid, 2-6 parts of terbium nitrate pentahydrate and 160-300 parts of ethanol are mixed, and the temperature is increased for reaction. After the reaction is completed, the ethanol is distilled off, and then vacuum drying is performed to obtain a 2-amino-5-fluorophenylboric acid / terbium complex.
7. The method according to claim 6, characterized in that The reaction temperature is 40-50°C and the reaction time is 80-160 minutes.
8. The method according to claim 1, characterized in that The ionic liquid is selected from one of [EMIM][PF6], [BMIM][PF6], [HMIM][PF6], [EMIM][TF2N], [BMIM][TF2N], [HMIM][TF2N], [EMIM][DCA], [BMIM][DCA], and [HMIM][DCA].
Citation Information
Patent Citations
An ionic conduction film having a microphase separation structure, and preparation and applications thereof
CN107546398A
Method for preparing beta-diketone functional rare-earth organic luminous gel based on silicon-boron composite network
CN102002359A
Preparation method of rare-earth-ion-doped cerium fluoride hollow nano microsphere
CN103979595A
Polyethyleneimine binder complex films
US5672465A
